The Role of Benevolence Trust as Mediating Variable in Improving Patients' Decisions in Choosing Inpatient Services at Class C Hospital - Entin Kartikasari; Rokiah Kusumapradja; Intan Silviana Mustikawati (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
As one of the oldest hospitals in Bekasi Regency, KM I Hospital is required to remain trusted by patients in choosing health services including inpatient care. The decline in BOR (Bed Occupancy Rate) experienced by KM I Hospital in the last 1 year indicates that hospital marketing needs to be improved.  This study aims to analyze the effect of competitive advantage and informational reference groups on patient's decision in choosing inpatient services with benevolence trust as an intervening variable at KM I Hospital. The research method uses a quantitative explanatory research approach. Respondents were 185 patients at KM I Hospital who were willing to be hospitalized. The sample collection technique was purposive sampling. Data collection used a questionnaire, and the data analysis technique used SEM-PLS. Results show that Competitive Advantage and Informational Reference Group have a direct and indirect effect on patient’s decision to choose inpatient services through benevolence trust at KM I Hospital (p<0.05). These results theoretically support previous theories and research. Managerially, it is expected to provide input for KM I Hospital management to increase competitive advantage and strengthen informational reference groups. These efforts can increase benevolence trust and ultimately increase patient’s decision to choose inpatient services.